Financial Wellbeing of Older Persons in Peninsular Malaysia - Chan, Benjamin Yin Fah (2005)
The purpose of the study was to investigate the financial wellbeing of older Malaysians and its association with fmancial status, financial literacy, money attitude, financial practices and financial problems. Data for h s cross-sectional study was obtained through interview with 1,841 older persons (55 years and above) in Peninsular Malaysia. Systematically, Seventy-five out of the national total 1,173 sub-&vision/muh (provided by Department of Statistic) was chosen and four Enumeraaon Blocks (EBs) with hghest number of older persons age 55-75 were selected from each sub-&vision. The findmgs of the study revealed that majority of older Malaysians have negative net worth, low in financial literacy, money attitude and moderate financial practices. One thud of the respondents have at least one financial problem over the last year. Respondents who are financially literate have less financial problems. A sipficant relationshp was found between money attitude and financial practices, and also between financial practices and financial satisfaction. Determinants that sipficantly contributed to financial satisfaction were health, income adequacy, financial literacy, money attitude, fmancial practices, financial problems, net worth, home ownership, and ethnicity. However, through an open-ended question, some new factors such as comfortable life, able to cover expenses, pilgnrnage to Mecca, hardworking, phdanthropy are also contributed to the feelmg of financial wellbeing. It is important to educate the population about personal finance, inculcate a positive money attitude and financial practices to public as these d eventually lead to financial wellbeing of an individual.